2019
DOI: 10.1002/ceat.201800742
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cypermethrin and Chemical Oxygen Demand from Livestock Wastewater by Electrocoagulation

Abstract: The direct discharge of wastewater from livestock into freshwater and surface runoff originating from processing areas threaten aquatic ecosystems and the quality of drinking water taken from streams. The present work studied the removal of chemical oxygen demand (COD) and cypermethrin (Cyp) from livestock wastewater generated after cattle baths by a continuous electrocoagulation (EC) process. The effect of pH, retention time, and voltage on COD and Cyp removal was examined. Under the optimal operating conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The samples were centrifuged at 7500 r·min –1 for 15 min, the supernatant was passed through a 0.45 μm water filtration membrane, and the soluble components were collected. The American Public Health Association methods were used to determine the soluble chemical oxygen demand (sCOD) and NH 4 + -N content in the supernatant. The compositions of organic acids were determined by high-performance liquid chromatography .…”
Section: Methodsmentioning
confidence: 99%
“…The samples were centrifuged at 7500 r·min –1 for 15 min, the supernatant was passed through a 0.45 μm water filtration membrane, and the soluble components were collected. The American Public Health Association methods were used to determine the soluble chemical oxygen demand (sCOD) and NH 4 + -N content in the supernatant. The compositions of organic acids were determined by high-performance liquid chromatography .…”
Section: Methodsmentioning
confidence: 99%
“…Chemical treatment methods offer effective means of treating LWW to remove pollutants and improve its quality before discharge into the environment or reuse. Chemical treatment methods are usually applied in combination with physical and biological treatments to achieve maximum efficiency [ 134 , 135 ] or as a standalone process [ 13 , [136] , [137] , [138] , [139] , [140] , [141] ]. The most widely used chemical LWW treatment methods include precipitation, coagulation and flocculation, pyrolysis, electrocoagulation, adsorption, and Fenton processes, and can be optimized using RSM for better process performance and resource conservation ( Table 5 ).…”
Section: Application Of Rsm In Various Livestock Wastewater Treatment...mentioning
confidence: 99%
“…Electrochemical treatment, another popular LWW management approach that has attracted considerable attention in recent years. Among different electrochemical treatment technologies, electrocoagulation is most widely used due to its simplicity and ability to treat a wide array of pollutants including emerging contaminants present in LWW [ 138 , [143] , [144] , [145] , [146] , [147] ]. Regardless of electrode materials, parameters such as current density, pH, treatment time, electrolyte concentration, and interelectrode gaps are important for the successful and efficacious operation of electrocoagulation processes [ [148] , [149] , [150] , [151] ].…”
Section: Application Of Rsm In Various Livestock Wastewater Treatment...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the optimization of applied voltage in the electrochemical treatment of hazardous pollutants. 16,45,49 The RR4 degradation performance was evaluated at various applied voltages from 1, 5, 10, 15 to 20 V with an initial concentration of RR4 at 200 mg L −1 and 0.4 mol L −1 NaCl concentration f as the supporting electrolyte at pH 6 and 30 °C for 60 min electrolysis time.…”
Section: Effect Of Applied Voltagementioning
confidence: 99%